Matrix Metalloproteinase 3: A Promoting and Destabilizing Factor in the Pathogenesis of Disease and Cell Differentiation - Wan, Jiangtao; Zhang, Guowei; Li, Xin; Qiu, Xianshuai; Ouyang, Jun; Dai, Jingxing; Min, Shaoxiong (Frontiers in Physiology, 2021)
Cells must alter their expression profiles and morphological characteristics but also reshape the extracellular matrix (ECM) to fulfill their functions throughout their lifespan. Matrix metalloproteinase 3 (MMP-3) is a member of the matrix metalloproteinase (MMP) family, which can degrade multiple ECM components. MMP-3 can activate multiple pro-MMPs and thus initiates the MMP-mediated degradation reactions. In this review, we summarized the function of MMP-3 and discussed its effects on biological activities. From this point of view, we emphasized the positive and negative roles of MMP-3 in the pathogenesis of disease and cell differentiation, highlighting that MMP-3 is especially closely involved in the occurrence and development of osteoarthritis (OA). Then, we discussed some pathways that were shown to regulate MMP-3. By writing this review, we hope to provide new topics of interest for researchers and attract more researchers to investigate MMP-3.